2017
DOI: 10.1016/j.pec.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life parental communication priorities among bereaved fathers due to cancer

Abstract: Objectives To elicit widowed fathers’ perspectives on which domains of parenting-related communication they consider most important for dying parents to discuss at the end of life (EOL). Methods Two hundred seventy nine fathers widowed by cancer completed a survey about their own depression and bereavement symptoms, their wife’s illness, and EOL parental communication priorities. Chi square and Fisher’s exact tests and logistic regression were used to evaluate relationships between maternal EOL characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
1
7
0
1
Order By: Relevance
“…Several studies support that the parental status of being a PWAC with dependents impacts their end-of-life decisions, which also increases their worries and concerns. 4,17,18 However, this study acknowledged the PWACs' concern about the uncertainty in their coparent's abilities to make end-of-life decisions for them.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Several studies support that the parental status of being a PWAC with dependents impacts their end-of-life decisions, which also increases their worries and concerns. 4,17,18 However, this study acknowledged the PWACs' concern about the uncertainty in their coparent's abilities to make end-of-life decisions for them.…”
Section: Discussionmentioning
confidence: 83%
“…[1][2][3] When a patient has advanced cancer and is a parent to dependents (PWAC), the patient's concerns are increased, thereby impacting the patient's quality of life, psychological well-being, and perceived family functioning. 1,4,5 Yet, the literature on the approaching death of PWAC has often been limited to the term "parental concerns," [5][6][7][8][9] rather than the broader concept of dying concerns. Plus, the extant literature has mainly focused on concerns related to the PWAC's children, with limited focus on the concerns for the coparent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…W przypadku, gdy partnerzy nie mieli okazji ustalić wspólnej strategii dalszej opieki nad dzieckiem przez pozostającego przy życiu rodzica, późniejsza samotna już rola opiekuna może nastręczać wiele problemów, co jest z reguły znacznie trudniejsze dla ojców. Doświadczając choroby i następnie śmierci partnerki-matki, wielu mężczyzn żywi przekonanie, że nie otrzymało od niej właściwej "instrukcji", jak postępować z dzieckiem (dziećmi), zarówno w odniesieniu do sytuacji przeżywania straty, jak i w innych kwestiach życiowych [16].…”
Section: Dziecko W Sytuacji żAłobyunclassified
“…Little research has explored experiences of single parents with minor children . For example, one study indicated that healthy parents were keen to reassure and protect children, but that they failed to provide sufficient cancer‐related information.…”
Section: Introductionmentioning
confidence: 99%